2016
DOI: 10.1021/acs.cgd.6b00554
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphs, Hydrates, Cocrystals, and Cocrystal Hydrates: Thermodynamic Modeling of Theophylline Systems

Abstract: Polymorphic transitions and hydrate formation often occur in systems of cocrystal-forming components. To increase the efficiency of cocrystal formation and purification processes, the complex phase behavior of such systems was modeled using PC-SAFT. This is demonstrated for theophylline, a well-studied pharmaceutical, exhibiting polymorphs, as well as formation of a hydrate, cocrystals, and even cocrystal hydrates. The solubility of theophylline in water was modeled including hydrate formation (1:1) as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 104 publications
1
24
0
Order By: Relevance
“…Theophylline belongs to a class of organic solutes that exhibit rich structural diversity in the solid-state. The commercial theophylline is usually offered in the form of polymorph II since it easily crystallises from many neat organic solvents [ 87 , 88 , 89 ], and for a long time, it was considered to be the most stable form thermodynamically at room temperature [ 87 , 90 , 91 ]. However, it was documented by Seton et al [ 89 ] that form IV is more stable at ambient conditions, although the II → IV conversion encounters a kinetic barrier significantly slowing the spontaneous transformation [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theophylline belongs to a class of organic solutes that exhibit rich structural diversity in the solid-state. The commercial theophylline is usually offered in the form of polymorph II since it easily crystallises from many neat organic solvents [ 87 , 88 , 89 ], and for a long time, it was considered to be the most stable form thermodynamically at room temperature [ 87 , 90 , 91 ]. However, it was documented by Seton et al [ 89 ] that form IV is more stable at ambient conditions, although the II → IV conversion encounters a kinetic barrier significantly slowing the spontaneous transformation [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, CNIBS/R-K and the modified Jouyban−Acree models were applied for interpreting the solubility of theophylline in methanol-water and isopropanol-water conditions [ 86 ]. Moreover, rich solid-liquid phase diagrams of theophylline were computed using the same set of parameters in PC-SAFT modelling [ 90 ]. Besides, preferential solvation of theophylline in methanol-water mixtures was characterised using the same idea [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…A separate group of hydrates form hydrated co-crystals, which are quite common among obtained forms of APIs. Despite being more complex than simple hydrates, their analysis unfolds with application of the same methods [ 62 , 110 , 111 , 112 , 113 , 114 , 115 ].…”
Section: Hydrates Structural Analysis Selected Cases Within the Lmentioning
confidence: 99%
“…However, depending on the system, the mutual influence on solubility of API and CF might be tremendous. To account for these nonidealities, thermodynamic activities of the solutes (API and CF) have to be considered. Zhang et al used the thermodynamic activity of the CF to obtain the critical CF activity, at which the CC is more stable than the API crystal. Lange and Sadowski showed that the concentration window for CC formation in solvents and solvent mixtures can be predicted based only on one solubility data point of each API, CF, and CC in any solvent.…”
Section: Introductionmentioning
confidence: 99%